2020
DOI: 10.1039/d0ra09112j
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and bioevaluation of novel 6-substituted aminoindazole derivatives as anticancer agents

Abstract: In the present study, a series of 6-substituted aminoindazole derivatives were designed, synthesized, and evaluated for bio-activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…41,42 Moreover, molecular docking simulations have also been utilized to interpret the experimental data, especially when the experimental structures were not available. 43…”
Section: Computational Methods and Applicationsmentioning
confidence: 99%
“…41,42 Moreover, molecular docking simulations have also been utilized to interpret the experimental data, especially when the experimental structures were not available. 43…”
Section: Computational Methods and Applicationsmentioning
confidence: 99%
“…Our previous study indicated that the indazole scaffold plays an important role in interaction with IDO1 active site residues at pocket A, and the 6-NH group in the 6-aminoindazole template also forms hydrogen bond (HB) with the 7-propionate of the heme ion (Figure 2B) 14 .…”
Section: Introductionmentioning
confidence: 99%